Analisis Pembelajaran Sains Di Kalamullah Al-Quran And Multilingual School Thailand - Nono Triwijayanto; Siti Niah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This study analyzes the science learning process at Kalamullah Alquran and Multilingual School in Thailand. This study is a qualitative research employing methods of literature review, interviews, and observations. It was found that integrating Quranic teachings with science provides holistic understanding to students. The multilingual environment presents challenges in communication and understanding scientific concepts. Limitations in time and student numbers affect teaching methods, while low student engagement is due to lax rules on cellphone usage. The school's infrastructure is adequate, but projectors and science laboratories are limited. The low usage of laboratories is due to constraints in practical kits and time. Recommendations include better time management, stricter rules on cellphone usage, and increased utilization of facilities to enhance the effectiveness of science learning.